Anthropometric and laboratory characterization of patients tested for SARS-CoV-2 at the Hospital of the Military Policeman of Goiânia-GO (Research, Society and Development, 2022)
Objective: to find changes between laboratory tests of patients tested for COVID-19. Methodology: An observational analytical study was carried out with military personnel and their family members over 18 years of age who were tested for COVID-19 and were followed up at the Hospital do Policial Militar. A comparative analysis was performed between anthropometric data, age group, sex and the following tests: C-reactive protein (CRP), D-dimer, erythrocyte sedimentation rate (ESR), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and lactate dehydrogenase (DHL), ferritin, urea, creatinine, creatine kinase (CK) and troponin I. A descriptive analysis was performed, with mean and standard deviation, in addition to the f test and the ANOVA test with a significance level (p < 0.05). Results: Of the total of 4499 patients, 2646 (59%) were male and 3094 (69%) subjects had undetected RT-PCR for SARS-CoV-2. The lowest mean age was female, 28 years (±13.55) and the highest total BMI, 27.81 (±4.45), both in the detected/inconclusive group. Furthermore, the group with detected/inconclusive RT-PCR had significantly higher D-dimer, CRP, AST, ALT, DHL, ferritin and creatinine than the undetected group. Conclusion: It was possible to observe a significant relationship between obesity, COVID-19, male gender and advanced age (above 51 years old) with an increase in laboratory test values (p